PENGARUH KOMUNIKASI INTERPERSONAL DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT PLN (PERSERO) UNIT PELAKSANA PELAYANAN PELANGGAN (UP3) BALI TIMUR - Kadek Bayu Wedana; I Wayan Sukadana; I Wayan Suarjana (EMAS, 2022)
Employees are the main driver of every organization. Without them, organizations and other resources would never be meaningful. So to be able to achieve the goals to be achieved by an organization required employees who have good performance. Employee performance is something that can affect how much an organization's targets are achieved. The purpose of this study was to examine the effect of interpersonal communication and organizational commitment on employee performance. This research was conducted at PT PLN (Persero) UP3 East Bali. The number of respondents in this study were 71 people. Collecting data by distributing questionnaires using a Likert scale with a score of 1 to 5. The data analysis technique is a multiple linear regression analysis technique. Based on the results of multiple linear regression analysis, the influence of Interpersonal Communication (X1) and Organizational Commitment (X2) on the Employee Performance variable (Y) is positive, meaning that if interpersonal communication and organizational commitment increase, employee performance will increase and vice versa. Partially the interpersonal communication variable (X1) has a positive and significant effect on employee performance (Y) with a sig value of 0.000 <0.05. Likewise, the organizational commitment variable (X2) has a positive and significant effect on employee performance (Y) with a sig value of 0.000 <0.05. interpersonal communication, organizational commitment and employee performance have a very strong relationship seen from the correlation value (R) is 0.936 because it is in the 0.800 - 1,000 category.